Dinamika Teori dalam Realitas: Refleksi Guru Muda dalam Mengajar Bahasa Indonesia di MTs Aisyiyah Kota Binjai - Tambunan, Riskida; Manurung, Ruth; Ambarita, Yanti; Surip, M (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In practice, not all theories learned during teacher education can be applied directly in the classroom, thus creating a gap between theory and practice. This challenge is often faced by young teachers, including in teaching Indonesian at MTs Aisyiyah Binjai City. This study focuses on the reflection of a young teacher in dealing with this gap. Using a qualitative approach with a case study method, this study explores how critical reflection helps teachers evaluate teaching methods, understand the obstacles faced, and adjust strategies to classroom conditions. The results of the study indicate that reflection is not only an evaluation tool, but also a process of deconstructing theory that allows teachers to be more adaptive to student needs. These findings are expected to provide insight for young teachers in developing more effective and contextual teaching strategies